Functional Division Between the RecA1 and RecA2 Proteins in Myxococcus xanthus - Sheng, Duo-Hong; Wang, Yi-Xue; Qiu, Miao; Zhao, Jin-Yi; Yue, Xin-Jing; Li, Yue-Zhong (Frontiers in Microbiology, 2020)
Myxococcus xanthus DK1622 has two RecA genes, recA1 (MXAN_1441) and recA2 (MXAN_1388) with unknown differentiated functions. Herein, we showed that both recA genes were induced by ultraviolet (UV) irradiation, but the induction of recA1 was more delayed than that of recA2. Deletion of recA1 did not affect the growth, but significantly decreased the UV-irradiation survival, homologous recombination ability, and induction of the LexA-dependent SOS genes. In contrast, the deletion of recA2 markedly prolonged the lag phase of bacterial growth and DNA damage caused by hydrogen peroxide, but did not change the UV-radiation resistance and the SOS-gene inducibility. Protein activity analysis demonstrated that RecA1, but not RecA2, catalyzed DNA strand exchange and LexA-autocleavage in vitro. Transcriptomic analysis indicated that RecA2 has evolved to mainly regulate the gene expressions for cellular transportation and antioxidation. This is the first report of functional divergence of duplicated bacterial recA genes. The results highlight the evolutionary strategy of M. xanthus cells for the DNA homologous recombination and the evolution of genomes from simple to complex.